Comparing the Main Approaches of Image Segmentation - Amir Abdullah Karim, Abdul; Ali Sameer, Rafal (Iraqi Journal of Science, 2021)
Images are important medium for conveying information; this makes improvement of image processing techniques also important. Interpretation of image content is one of the objectives of image processing techniques. Image interpretation that segments the image to number of objects called image segmentation. Image segmentation is an important field to deal with the contents of images and get non overlapping regions coherent in texture and color, it is important to deal only with objects with significant information. This paper presents survey of the most commonly used approaches of image segmentation and the results of those approaches have been compared and according to the measurement of quality presented in this paper the Otsu's threshold method give the best result with less time.